Penerapan Metode Naïve Bayes Dalam Memprediksi Kepuasan Pelanggan Terhadap Pelayanan (Studi Kasus : Brastagi Supermarket Rantauprapat) - Putra, Fasdiansyah; Harahap, Syaiful Zuhri; Irmayanti, Irmayanti; Bangun, Budianto (Journal of Computer Science and Information System(JCoInS), 2025)
Supermarkets are crowded shopping centers and have a high potential for violations against consumers, especially because most of the products sold are basic foodstuffs. This study aims to predict the level of customer satisfaction with service in Brastagi supermarket Rantauprapat by applying the Naïve Bayes method of Data Mining algorithm. The primary data collection process is done through the distribution of online questionnaires using Google Form to customers. To ensure the validity of the data, further verification was carried out through direct interviews with customers as well as supermarket managers. The results of this study are expected to provide in-depth analysis and new information for the management of Brastagi Supermarket Rantauprapat regarding customer satisfaction, which can be used as a basis for improving service quality in the future.